Work Discipline Mediation: The Role of Employee Training and Competence in Improving Performance at BKPSDM Jember Regency - Sriwitantiningsih, Luluk; Herlambang, Toni; Martini, Ni Nyoman Putu; Qomariah, Nurul; Ku Mahamud, Ku Ruhana (PT Mattawang Mediatama Solution, 2024)
This study aims to explore the influence of employee training and competence on performance, both directly and through the role of work discipline as a mediating variable. This study is based on the problem of employee performance which has not met the expected target, characterized by a lack of work discipline and low efficiency in completing tasks. This study involved 56 respondents and used a quantitative method with a descriptive approach. Data were collected through questionnaires, and analysis was carried out using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the WarpPLS program. The results showed that training had an effect on employee work discipline and performance. Employee competence also had an effect on employee work discipline and performance. Work discipline as a mediating variable showed an indirect effect on performance, although its contribution was smaller than the direct effect of employee training and competence. The total effect of training on performance was 0.745, while the total effect of competence was 0.372. The implication of this study is the importance of organizations to improve relevant and sustainable training and develop employee competence development programs. Work discipline also needs to be strengthened through policies that encourage an organized work culture, such as providing incentives and effective supervision. With this strategy, it is expected that employee performance can be improved and organizational targets can be achieved optimally.